Humanistic burden of problem joints for children and adults with haemophilia. Issue 2 (27th December 2022) - Burke, Tom; Rodriguez‐Santana, Idaira; Chowdary, Pratima; Curtis, Randall; Khair, Kate; Laffan, Michael; Mclaughlin, Paul; Noone, Declan; O'Mahony, Brian; Pasi, John; Skinner, Mark; O'Hara, Jamie
Abstract: Introduction: The "problem joint" (PJ) concept was developed to address patient‐centric needs for a more holistic assessment of joint morbidity for people with haemophilia (PwH). Aim: To quantify the humanistic burden of PJs in PwH to further support validation of the PJ outcome measure. Methods: Multivariable regression models evaluated the relationship between PJs and health‐related quality of life (HRQoL, EQ‐5D‐5L) and overall work productivity loss (WPL) using data from the 'Cost of HaEmophilia: a Socioeconomic Survey' population studies (adults: CHESS II, CHESS US+; children/adolescents: CHESS‐Paeds). Covariates included were haemophilia severity, age, comorbidities and education. Results: The CHESS II sample included 292 and 134 PwH for HRQoL and WPL analyses, mean age 38.6 years (39% ≥1 PJ, 61% none). CHESS US+ included 345 and 239 PwH for HRQoL and WPL, mean age 35 years (43% ≥1 PJ, 57% none). CHESS‐Paeds included 198 PwH aged 4–17 (HRQoL only), mean age 11.5 years (19% ≥1 PJ, 81% none). In CHESS II and CHESS US+, presence of PJs was associated with worse HRQoL (Both p  < .001). Few CHESS‐Paeds participants had PJs, with no significant correlation with HRQoL. In CHESS II, upper body PJs were significantly correlated to WPL ( p  < .05). In CHESS US+, having ≥1 PJ or upper and lower body PJs were significantly correlated to WPL (vs. none; both p  < .05). Conclusion: This study has shown a meaningful burden of PJs on PwH, which should be considered in clinical and health policy assessments of joint health.